Quality Of Meat Rendang With Different Heating Tools - Bunga Walia; Wiwik Gusnita (Jurnal Pendidikan Tata Boga dan Teknologi, 2020)
Meat rendang is a traditional Minangkabau food. From generation to generation, the Minangkabau people from ancient times until now have used a heating device or traditional stove called a stove to make beef rendang. But along with the times, many types of modern stoves have emerged that are used to make beef rendang, one of which is a gas stove. Meat rendang is made by stirring continuously until it is dry. The heat produced by the stove and gas stove will have different temperature levels, this will affect the quality of the meat rendang produced. Based on the belief of the Minangkabau people that making rendang, it is better to use a wood-fired stove to get good results. This study aims to compare the quality of beef rendang using a stove and gas stove. This type of research is an experiment with organoleptic test. The study was conducted in 3 repetitions with 5 limited panelists. The data obtained were analyzed using the T test (t test). The results showed that the average value of the quality of the two beef rendang is almost the same. The average values for the quality of beef rendang using a stove and gas stove are forms, namely 3.00 and 2.93; the color of the inner flesh, namely 3.20 and 3.13; bran colors, namely 3.33 and 3.27; aroma, namely 3.80 and 3.47; meat texture, namely 3.07 and 2.93; bran texture, namely 3.13 and 2.93; and bran flavors, namely 3.87 and 3.60; and the taste of the meat, namely 3.40 and 3.20. Based on the results of the T test, it is stated that there is no significant difference between beef rendang using a stove and gas stove for each quality tested.